The coupling of the hydrated proton to its first solvation shell - Schröder, Markus; Gatti, Fabien; Lauvergnat, David; Meyer, Hans-Dieter; Vendrell, Oriol (Nature Communications, 2022)
The Zundel (H5O+2) and Eigen (H9O+4) cations play an important role as intermediate structures for proton transfer processes in liquid water. In the gas phase they exhibit radically different infrared (IR) spectra. The question arises: is there a least common denominator structure that explains the IR spectra of both, the Zundel and Eigen cations, and hence of the solvated proton? Full dimensional quantum simulations of these protonated cations demonstrate that two dynamical water molecules and an excess proton constitute this fundamental subunit. Embedded in the static environment of the parent Eigen cation, this subunit reproduces the positions and broadenings of its main excess-proton bands. In isolation, its spectrum reverts to the well-known Zundel ion. Hence, the dynamics of this subunit polarized by an environment suffice to explain the spectral signatures and anharmonic couplings of the solvated proton in its first solvation shell.
Gesehen am 17.01.2023